Can resistance training impact MRI outcomes in relapsing-remitting multiple sclerosis?. (September 2018) - Kjølhede, Tue; Siemonsen, Susanne; Wenzel, Damian; Stellmann, Jan-Patrick; Ringgaard, Steffen; Pedersen, Bodil Ginnerup; Stenager, Egon; Petersen, Thor; Vissing, Kristian; Heesen, Christoph; Dalgas, Ulrik
Background: Multiple sclerosis (MS) is characterised by accelerated brain atrophy, which relates to disease progression. Previous research shows that progressive resistance training (PRT) can counteract brain atrophy in other populations. Objective: To evaluate the effects of PRT by magnetic resonance imaging (MRI) and clinical measures of disease progression in people with MS. Methods: This study was a 24-week randomised controlled cross-over trial, including a Training ( n = 18, 24 weeks of PRT followed by self-guided physical activity) and Waitlist group ( n = 17, 24 weeks of habitual lifestyle followed by PRT). Assessments included disability measures and MRI (lesion load, global brain volume, percentage brain volume change (PBVC) and cortical thickness). Results: While the MS Functional Composite score improved, Expanded Disability Status Scale, lesion load and global brain volumes did not differ between groups. PBVC tended to differ between groups and higher absolute cortical thickness values were observed in 19 of 74 investigated cortical regions after PRT. Observed changes were confirmed and reproduced when comparing relative cortical thickness changes between groups for four areas: anterior cingulate gyrus, temporal pole, orbital sulcus and inferior temporal sulcus. Conclusion: PRT seem to induce an increase in cortical thickness, indicating that PRT have a neuroprotective or even neuroregenerative effect in relapsing-remitting MS.